THE EFFECT OF INQUIRY TRAINING LEARNING MODEL ON STUDENT CRITICAL THINKING SKILLS IN SMA NEGERI 1 STABAT - Nurkholilah, Nurkholilah; Ritonga, Winsyahputra ((IPER) Indonesian Physics Education Research, 2020)
This study was conducted to determine the effect of the Inquiry Training Model on students' critical thinking skills. This research design uses two group pretest-posttest technique. All of Student Class X in SMA Negeri 1 Stabat was the population of this research. Then two classes were selected as samples of the study, one class as an experimental class is taught using the Inquiry Training learning model while the other class as a control is taught using a conventional learning model. The research data collection instrument was in the form of 5 validated essay tests which would later be analyzed using the t test. The results of the study indicate that the inquiry training learning model has a significant impact on increasing students' critical thinking skills compared to students learning with conventional models on momentum and impulse material.Keywords: Inquiry Training, Critical Thinking Skill, Momentum and Impulse